Tumor-shrinking effects of enfortumab vedotin between primary urothelial carcinoma and metastatic organs - Ikarashi, Daiki; Kawamura, Tatsuya; Ogasawara, Keita; Arakawa, Yumeka; Machida, Arisa; Ito, Ayato; Shiomi, Ei; Maekawa, Shigekatsu; Kato, Renpei; Kanehira, Mitsugu; Sugimura, Jun; Obara, Wataru (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to determine and compare the tumor shrinkage rate and its durability by enfortumab vedotin treatment between primary urothelial carcinoma and metastatic organs.MethodsWe retrospectively evaluated the tumor shrinkage rate in 39 Japanese patients treated with enfortumab vedotin for advanced urothelial carcinoma. We also evaluated the periods of tumor shrinkage maintenance (the period when best response was maintained) and regrowth (the period from best response to tumor growth confirmation) between primary and metastatic organs.ResultsMeasurable metastatic organs included the lung in 17, lymph node in 22, liver in 6, and bone in 5 cases. Primary lesion was detected in 20 cases. The mean tumor shrinkage rates for lung, lymph node, liver, and bone metastases and primary sites were 21% (−212 to 100), 13% (−130 to 86), −8.5% (−158 to 85), −64% (−250 to 21), and 22% (−38 to 79), respectively. The tumor shrinkage was maintained for 5.9 (0.7–14) months in lung metastases, 8.3 (2.6–14.5) months in lymph node metastases, 3.6 months in liver metastases, 0.7 months in bone metastases, and 1.8 (0.7–5.4) months in primary sites, and the period of regrowth was 7.3 (2.2–19.4), 4.8 (2.0–8.9), 2.8, 6.5, and 2.5 (1.1–5.9) months, respectively.ConclusionsEnfortumab vedotin showed significant tumor shrinkage in the primary tumor, lung metastases, and lymph node metastases, whereas the durability of tumor shrinkage was limited in the primary tumor.